Effect of time of court and maturing of the silage of Tithonia diversifolia in the in vivo digestibility, used as supplement in sheep (Revista Sistemas de Producción Agroecológicos, 2014)
In the tropical zone of Colombia, nutrition is the most influential factor of productive and reproductive processes of ruminant, therefore, the objective of this work was to evaluate the effect of cut age of Tithonia diversifolia (Td) and the degree of maturity of silage on the nutritional quality and digestibility in vivo in crossbred sheep hair as a supplement to a basal diet of King grass (Pennisetum purpureum) (PP). Leveling pruning was done after three cuts: 45, 60 and 75 days, 25% silages were mixed: 75% molasses (TdS). For digestibility nine sheep were used with average weight 30 kg ± 5kg, were fed adlibitum and PP 400 g dry matter (DM) of TdS. Diets and excreta were evaluated in laboratory Nutrition. Completely randomized design, nine treatments concerning the three cuts and three maturation TdS was used: 30, 45 and 60 days, with three replications. When conducted fieldwork and laboratory values of the nutritional quality of silage were on average: MS (21.7%), protein (12%), and content of neutral detergent fiber (NDF) below 40 %. Apparent digestibility of DM (DAMS) was higher than 60% with an average 68.5 ± 5.5%. Regarding the digestibility of crude protein (CPD), as this is affected increases cutting time, but a longer maturation TdS maintain or increase its digestibility, resulting in average: 62.3 ± 9.9%.
Keywords: sheep; silage; in vivo digestibility; Tithonia diversifolia